Association between bone mineral density and cardiovascular disease in older adults - Yang, Yulu; Huang, Yun (Frontiers in Public Health, 2023)
Background and aims Cardiovascular disease and osteoporosis are common diseases in older adults with high morbidity. The study on the interaction between the two in pathogenic mechanisms has been paid much attention by the majority of researchers. This study aimed to explore the relationship between bone mineral density and cardiovascular disease in older adults. Methods The primary data was downloaded from the National Health and Nutrition Examination Survey database of the United States. Multivariate logistic regression model, generalized additive model, and smooth curve fitting were used to explore the relationship between bone mineral density and cardiovascular events risk. When a curve relationship was found, a two-piecewise linear model was used to calculate the inflection point. In addition, subgroup analysis was also performed. Results A total of 2097 subjects were included in this study. After adjusting for potential confounders, no significant association was found between lumbar bone mineral density and cardiovascular disease, while femur bone mineral density had a non-linear relationship with cardiovascular disease, with an inflection point of 0.741 gm/cm2. When bone mineral density was <0.741 gm/cm2, the risk of cardiovascular disease decreased speedily. Once bone mineral density exceeded this value, the risk of cardiovascular disease continued to decrease, but the trend became significantly slower. Compared with patients with normal bone mass, osteoporosis was associated with a 2.05-fold increased risk of cardiovascular disease (95% CI 1.68–5.52). There were no significant differences in interaction tests of all subgroups (p for interaction >0.05) except race. Conclusion Our results indicated that bone mineral density was closely associated with the prevalence of cardiovascular disease in older adults over 60 years old, especially the femur bone mineral density was negatively non-linear associated with cardiovascular disease risk, with an inflection point of 0.741 gm/cm2.